Sistem Pengoperasian Bongkar Muat Barang dan Keterkaitan Spasial Arus Barang di Pelabuhan Tanjung Wangi Kabupaten Banyuwang - , IMELDA PRIMA VALENTINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is an archipelago country which has a lot of natural resources potential that needs to be used and distributed in order to fulfill all areas needs. The role of a harbor as a trading gate is very important for the sake of loading and unloading goods. The unavailable harbor facilities can affect the number of ships which stopover in order to load and unload goods. This research aims (1) to analyze the goods loading and unloading system at Tanjung Wangi harbor, (2) to analyze the correlation of goods stream spatial at Tanjung Wangi harbor, (3) to analyze the relationship between the goods loading and unloading system with the goods stream spatial correlation at Tanjung Wangi harbor. First methods in this research using qualitative analysis (for analysis goods loading and unloading system at Tanjung Wangi Harbor). Second methods using gravity analysis (for analysis goods stream spatial correlation at Tanjung Wangi Harbor) and the third aims, using getis ord g analysis (for analysis correlation between loading and unloading system with stream spatial). Based on the research, it can be concluded that: 1. Goods loading and unloading system was done based in the procedure starting from the arriving ships submitted the shipping documents to ADPEL and PT. Pelindo III then preparing service and set the location. Goods loading and unloading system perform a stevydoring, cargodoring, receiving or delivery and ships can leave the harbor after finish